Supervision Effectiveness DPS Deep Sharia Governance and Guarantee in Sharia Banking in Indonesia - Azhar, M. Elfi; Fela Yudha, Syuhada; Sugianto; Muda, Iskandar (Best Journal of Administration and Management, 2022)
Islamic banking, an indicator of the development of the Islamic economy in Indonesia, where if the Indonesian people are asked about the Islamic economy, then the first thing to highlight is Islamic banking. Currently, the increase in Islamic financial institutions such as Islamic banks has increased significantly. Banuak people who are currently starting to believe in sharia mining lemabags, even so Islamic banks must continue to supervise products in Islamic banks. In the development of Islamic financial institutions, it is certainly inseparable from the Sharia Supervisory Board, which is one of the characteristics compared to conventional banks. Sayriah financial institutions have DPS in governance, where this DPS has a function to supervise the application of sharia principles in each product, besides that DPS must also supervise sharia guarantees, both from the guarantee mechanism to the execution of guarantee collection carried out by Islamic financial institutions.